Strategi Pemberdayaan Masyarakat Dalam Pengembangan Kewirausahaan (Entrepreneurship) di Daerah PenyanggaTaman Nasional Ujung Kulon (TNUK) Pandeglang – Banten - Bukhari, Ahmad; Saleh, Khaerul (Journal of Economics and Economic Education, 2024)
The results of the research are that the main strength factor is having agricultural land land that is very adequate for developing entrepreneurship in the agricultural sector. The main weakness factor is that many people have not participated in training to develop business management skills. The main opportunity factor is the government's increasingly serious efforts to increase the number of entrepreneurs, both in the agricultural and non-agricultural sectors. And the main threat is the free flow of trade which causes losses if people are unable to compete. The strategy for developing an entrepreneurial spirit is a progressive strategy, which means the community is strong and has the opportunity to develop an entrepreneurial spirit. And the most priority strategy is to encourage Human Resources who have the potential to have educational knowledge, skills and attitudes.